2022
DOI: 10.1088/1748-9326/ac6002
|View full text |Cite
|
Sign up to set email alerts
|

The trend shift caused by ecological restoration accelerates the vegetation greening of China’s drylands since the 1980s

Abstract: Satellite observations since the early 1980s have revealed a trend of “Earth greening” across global terrestrial ecosystems. Dryland vegetation is more sensitive to climate change and human activities. China's drylands are among the largest in extent worldwide, and large-scale ecological restoration of these areas has been implemented since the late 1970s, which has resulted in more complicated but still poorly quantified vegetation dynamics. To figure out the vegetation dynamics and associated driving forces,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…These positive temperature-associated couplings combined with multiple water and biological cycles resulted in high atmospheric moisture demand, which made an active impact to the earlier BPs and widespread reduction in ER after BPs (figure 2). Together, the present spatiotemporal results demonstrated that the relationships between ER and climate conditions varied among different regions and were also influenced by ocean-atmospheric circulations (figure S10) (Kim et al 2019, Wang et al 2022. Our comprehensive analysis provides important findings that help understand the response of ecosystem functions to terrestrial-atmospheric variables.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…These positive temperature-associated couplings combined with multiple water and biological cycles resulted in high atmospheric moisture demand, which made an active impact to the earlier BPs and widespread reduction in ER after BPs (figure 2). Together, the present spatiotemporal results demonstrated that the relationships between ER and climate conditions varied among different regions and were also influenced by ocean-atmospheric circulations (figure S10) (Kim et al 2019, Wang et al 2022. Our comprehensive analysis provides important findings that help understand the response of ecosystem functions to terrestrial-atmospheric variables.…”
Section: Discussionsupporting
confidence: 51%
“…This has also been widely used as an alarm system to provide information on when and where changes have occurred using the R packages' bfast' , 'tseries' , and 'rlang' . The shortest segment was set to 0.25 of the total data length to limit the minimum number of observations in each segment (Li et al 2022). The most significant BPs were tested using the Chow test (P < 0.05) (Verbesselt et al 2012).…”
Section: Breakpoint (Bp) Identification and Trends In Ermentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al (2021a) analyzed the effects of 13 large-scale land conservation and restoration programs and found that more than 45% of China’s drylands experienced a significant increase in the normalized difference vegetation index. Since the early 2000s, vegetation greenness has increased by 6.7% (31.6 Mha) in China’s drylands as a direct result of restoration, especially in the Loess Plateau and the so-called Three-North region (Li et al, 2022b). Vegetation cover change in the last two decades in northern China has been especially prominent, where, for example, in Inner Mongolia, annual land cover changes exhibited a net forest increase of more than 190,000 ha during 2001–2014 in the areas where ecological programs have been conducted (Yin et al, 2018; Niu et al, 2019).…”
Section: China’s Research Progressmentioning
confidence: 99%